El comportamiento demográfico tradicional: la ciudad de León en la segunda mitad del siglo XIX - Brel Cachón, María Pilar (Estudios humanísticos. Geografía, historia y arte, 1990)
With data from García y Ponce de León, Nineteenth century Doctor from León, in his Topografía Médica de León, there can be analised the demographic characteristics of this town in the late last century. As de rest of the province capitals has a positive real growth which is not related with his own natural growth, where deceases exceed births due to the infant ages high mortality and the importance of the exogenous diseases. It’s a demographical behaviour form a pre-industrial economic and social organisation that has changed to ofter absolutely different characteristics nowadays.